ANTIBACTERIAL EFFICACY OF PLECTRANTHUS AMBOINICUS EXTRACTS AGAINST STREPTOCOCCUS MUTANS- AN INVITRO STUDY - Nikhil, *Krithi; Yavagal, Puja C. (International Journal of Ayurveda and Pharma Research, 2015)
Background: Dental caries continues to be a major oral health problem affecting people in developing and developed countries. Mechanical plaque control with chemical plaque control as an adjunct is used to prevent biofilm formation. The art and science of utilizing the medicinal properties of the herbs in Ayurveda is well documented. Increased incidences of documented side effects of the allopathic drugs with ever increasing cost of the same has paved way for a renewed interest in the concept of Ayurveda. Plectranthus amboinicus, a medical plants known to possess antimicrobial, antiepileptic and antioxidant properties. It has proven efficacy against a host of micro-organisms and may also be effective against Streptococcus mutans. Aim: The present study aims to find out the antibacterial efficacy of Plectranthus amboinicus extract against Streptococcus mutans. Materials and methods: Aqueous and ethanolic leaf extracts of Black Plectranthus amboinicus were prepared. The antibacterial efficacy was tested against Streptococcus mutans through Disc Diffusion Test and Minimum Inhibitory Concentration (MIC) Test. Results: S. mutans was found to be sensitive to ethanolic and aqueous extracts of Plectranthus amboinicus at two dilutions with MIC 50 µg/ml. Conclusion: The ethanolic and aqueous extracts of Plectranthus Amboinicus exhibited antibacterial effect against Streptococcus Mutans in vitro.